2023
DOI: 10.3390/s23062938
|View full text |Cite
|
Sign up to set email alerts
|

Computer Vision Applications in Intelligent Transportation Systems: A Survey

Abstract: As technology continues to develop, computer vision (CV) applications are becoming increasingly widespread in the intelligent transportation systems (ITS) context. These applications are developed to improve the efficiency of transportation systems, increase their level of intelligence, and enhance traffic safety. Advances in CV play an important role in solving problems in the fields of traffic monitoring and control, incident detection and management, road usage pricing, and road condition monitoring, among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 338 publications
0
5
0
Order By: Relevance
“…The main contributions of this paper are to reveal the data source, data processing, algorithm selection, and model evaluations used by recent research and to provide emerging research opportunities from a different point of view that focuses on the technical aspect of ML applications. These two contributions make this paper different from the existing surveys and reviews [15,16].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The main contributions of this paper are to reveal the data source, data processing, algorithm selection, and model evaluations used by recent research and to provide emerging research opportunities from a different point of view that focuses on the technical aspect of ML applications. These two contributions make this paper different from the existing surveys and reviews [15,16].…”
Section: Introductionmentioning
confidence: 91%
“…However, it was found that limited literature mainly focuses on detecting traffic flow anomalies. To the best of our search of existing surveys and reviews about traffic flow anomaly detection using ML, two published survey and review papers partially like our paper [15,16]. The limitations of these papers have been identified and can be explained as follows.…”
Section: Introductionmentioning
confidence: 99%
“…In the current era, computer vision research lines mention several approaches for vehicle classification and detection [15]. Thirumarai and Amudha [13] proposed a novel video surveillance technique with an image segmentation algorithm to track moving objects in a crosswalk of a road.…”
Section: Related Workmentioning
confidence: 99%
“…LDWS, a key component in advancing driver assistance technologies, actively contributes to road safety by alerting drivers of unintentional lane deviations [ 6 , 7 , 8 , 9 , 10 ]. The performance of LDWS is dependent on the clarity and detectability of road markings, which can be influenced by factors such as weather, wear, and lighting conditions [ 11 , 12 , 13 ]. That is, this system’s functionality is intricately linked to environmental factors, particularly road marking visibility and conditions.…”
Section: Introductionmentioning
confidence: 99%